2011
DOI: 10.1111/j.1551-2916.2011.04888.x
|View full text |Cite
|
Sign up to set email alerts
|

Large Piezoelectric Coefficient in (Ba1−xCax)(Ti0.96Sn0.04)O3 Lead‐Free Ceramics

Abstract: Lead-free (Ba 1Àx Ca x )(Ti 0.96 Sn 0.04 )O 3 (BCST) (x = 0-0.04) ceramics were prepared using solid-state reaction technique. At room temperature, a polymorphic phase transition from orthorhombic phase to tetragonal phase was identified in the composition range of 0.01x 0.03. Extremely high piezoelectric coefficient of d 33 = 510 pC/N and high planar electromechanical coupling factor of k p = 48% were obtained for the BCST ceramics at x = 0.02. These results indicate that the BCSTs are promising candidates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 23 publications
(41 reference statements)
5
36
0
Order By: Relevance
“…1(b) to detect difference among these samples. It can be seen that peak intensity in the right side becomes stronger with increasing Tb content, which confirms that a composition-dependent phase evolution from orthorhombic to tetragonal phase has happened [21,22]. In addition, it is known that for stable trivalent ions, small ion (ro0.87 Å) would occupy B-site, large ion would occupy A-site (r40.94 Å), and intermediate ion could occupy both A-site and B-site [23,24].…”
Section: Methodssupporting
confidence: 79%
“…1(b) to detect difference among these samples. It can be seen that peak intensity in the right side becomes stronger with increasing Tb content, which confirms that a composition-dependent phase evolution from orthorhombic to tetragonal phase has happened [21,22]. In addition, it is known that for stable trivalent ions, small ion (ro0.87 Å) would occupy B-site, large ion would occupy A-site (r40.94 Å), and intermediate ion could occupy both A-site and B-site [23,24].…”
Section: Methodssupporting
confidence: 79%
“…1a) and low measured density and relative density of 4.66 g/cm 3 and 78% ( Fig. 1 h), confirming that dense BCTS ceramic is difficult to be obtained below 1250 ƕ C since the densification T S has so far been reported to be 1450-1540 ƕ C. [5][6][7][8][9][10][11] After adding LiF, a developed dense microstructure with enlarged grains of 5-20 ȝm (Fig. 1b-f) and high relative density over 90% (Fig.…”
Section: Introductionsupporting
confidence: 78%
“…At present, the highest d 33 reaches 697 pC/N in BaTiO 3 -11BaSnO 3 ceramic at 40 ƕ C. [12] Outstanding piezoelectric properties of these BCTS ceramics are owing to coexisting two or more phases, which can lead to the instability of the polarization state that makes the polarization direction easily rotated by external stress or electric field. [5][6][7][8][9][10][11][12][13][14] Despite of their high piezoelectric properties, dense BaTiO 3 -based ceramics must be sintered at high temperature of 1400-1500 °C, which impedes practical applications. It is well known that LiF and LiF-containing additives 3 are very effective in lowering sintering temperature (T S ) and improving density for BaTiO 3 ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [24] and other authors [25,26,27] have recently reported that the (Ba,Ca)(Ti,Sn)O 3 ceramics with high d 33 values are promising candidates for lead-free piezoelectric ceramics. However, it is not easy to find balance between lowering the sintering temperature and maintaining good piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%